IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI DESA MPANAU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Sahempa, Muh. Rifai (Katalogis, 2014)
The objective of this research was to analyze the implementation of village fund allocationpolicy in Mpanau Village Sigi Biromaru Subdistrict Sigi Regency and the factors that influencing the implementation of the policy. The research used of theory implementationÂ Â  Edward III. The techniques of data collection were observation, interview and documentation. The data were analyzed qualitative descriptively. The research results showed that the implementation of village fund allocation policy in Mpanau Village Sigi Biromaru Subdistrict Sigi regency was not effective. It was seen from the four indicators of implementation policy such as Communication, Resources, Disposition and Bureaucratic Structure. Have not run well and the factors that influencing the implementation of policy Mpanau Village Sigi Biromaru Subsdistrict Sigi Regency which were society participation, working environment and regional condition.